Semantische Spezialisierung vs. Polysemie Interpretationsbesonderheiten bei Komplementreduktionen lexikalischer Einheiten - von der Becke, Tanja (Linguistik - Impulse & Tendenzen, 2021)
Transitive verbs can often leave their arguments implicit. Until now, the objectless variants of these verbs have been frequently associated with specific meanings. This volume demonstrates that most verbs have different interpretations with different valency frames and specific conditions for omission. Accordingly, statements about omission and their semantic consequences must be applied to the interpretations of a verb.